Ancient and modern Israel : an exploration of political parallels - Sharkansky, Ira. (Albany : State University of New York Press, 1991)
Annotation Sharkansky (political science, Hebrew U. of Jerusalem) identifies and examines those parallels between ancient and modern Israel that help to clarify the modern conflicts, discussing such contemporary issues as the Arab uprising and the Israeli government's ambivalence in dealing with it; the government's inability to come to a permanent solution concerning the territories occupied in 1967; and the lack of a clear-cut consensus in the 1988 elections. Annotation copyrighted by Book News, Inc., Portland, OR.
Front Matter -- Half Title Page -- Title Page -- Copyright Page -- Dedication Page -- Table of Contents -- Preface -- Content -- Clues in Ancient History -- Reading Jewish History -- The Ancient Country -- Modern Israel -- Historic Parallels and Their Implications -- Back Matter -- Notes -- Index -- Back Cover.
Includes bibliographical references (pages 159-181) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Jews -- Politics and government -- To 70 A.D.; Politics in the Bible; Israel -- Politics and government; Juifs -- Politique et gouvernement -- Jusqu'à 70.; Politique dans la Bible; Israël -- Politique et gouvernement; HISTORY -- Ancient -- General; Jews -- Politics and government; Politics and government; Politics in the Bible; Israel; To 70